Effect of physical activity intervention on physical activity, body mass index, blood pressure, blood lipid and fasting blood sugar among overweight and obese military personnel - Ahmad Fuad, Ahmad Farhan; Ismail, Suriani; Abdul Rahman, Hejar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: About 18% of Malaysian Armed Forces (MAF) personnel are diagnosed with either hypertension, diabetes or coronary artery disease, while another 8% are obese. The rising prevalence necessitates intervention. Methods: This is a single blinded randomized controlled trial among overweight and obese MAF personnel attending medical checkup in MAF hospital in Kuala Lumpur. An intervention module was developed to increase their physical activity level. Short version of International Physical Activity Questionnaire was used to assess physical activity in metabolic equivalent of task score (METs score), while blood pressure, body mass index (BMI), blood lipid profile and fasting blood sugar measurements were also obtained. These parameters were measured at baseline and again at 6 months. Generalized estimating equations (GEE) statistical test were applied to evaluate the effect of the intervention. Results: Response rate was 100%. Most of participants were aged above 40 years, male, from Malay ethnic group, completed secondary education and had monthly income above RM 4000. Most of the respondents were obese and had moderate level of physical activity at baseline. All variables compared between groups at baseline showed no significant difference. At six months, after controlling for covariates, the significant difference was only in METs score. The odds of having high METs score in the intervention group after receiving intervention was nearly 3 times higher than those in the control group, after adjusting for interaction between time and group as well as other covariates (AOR = 2.908, 95% CI 1.323 – 6.391, P=0.008). Conclusion: Intervention was effective in increasing physical activity among overweight and obese military personnel.